Hubungan antara Dukungan Tenaga Kesehatan dengan Pengetahuan Hipertensi dan Pola Diet Pasien Hipertensi di Poli Penyakit dalam RSI Sultan Agung Semarang - Endang Purwati; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Pusat Riset dan Inovasi Nasional, 2025)
Hypertension is one of the non-communicable diseases with a high prevalence, both globally and nationally, including in Indonesia. Proper support from healthcare providers plays a crucial role in improving knowledge and dietary adherence among hypertensive patients. This study aims to examine the relationship between healthcare support and knowledge of hypertension as well as dietary patterns among hypertensive patients in the Internal Medicine Clinic at RSI Sultan Agung Semarang. The study uses a quantitative design with a cross-sectional approach, involving 140 respondents selected through purposive sampling. The results indicate that the majority of patients receive good healthcare support, possess adequate knowledge of hypertension, and follow a good dietary pattern. However, Chi-Square test results show no significant relationship between healthcare support and knowledge of hypertension (p = 0.319) or dietary patterns (p = 0.319). This suggests that other factors, such as education, experience, family support, personal motivation, and eating habits, also influence the knowledge and dietary patterns of patients. In conclusion, although healthcare support plays a role in improving knowledge and dietary adherence in hypertensive patients, other external factors contribute significantly to the outcomes.